Radiance Contrasts at Possible Lunar Water Ice Exposures Seen by ShadowCam - Jordan Ando; Shuai Li; Mark Robinson; Robert Wagner (The Planetary Science Journal)
Surface water ice within lunar permanently shadowed regions (PSRs) could have an enhanced visible wavelength reflectance relative to lunar regolith. Moon Mineralogy Mapper (M ^3 ) infrared spectroscopic detections compose one data set previously interpreted as surface ice occurrences within the PSRs. Here we investigate the M ^3 water ice identifications at higher resolution with broadband visible-wavelength mosaicked images (60 m pixel scale) obtained by the ShadowCam instrument aboard the Korea Aerospace Research Institute Korea Lunar Pathfinder Orbiter. Individual M ^3 positive water ice detections show no radiance contrast with their surroundings. However, north polar PSRs with at least one M ^3 water ice detection have a ∼4.4× higher modal radiance than those lacking M ^3 water ice detections, although this cannot be definitively attributed to water ice. Our findings are consistent with previous estimates of ice abundance as being less than ∼30 wt%, resulting in contrast too small to be detected by the ShadowCam instrument.